2022
DOI: 10.1097/icb.0000000000001057
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab for Post Vitrectomy Cystoid Macular Edema in a Silicone Oil–filled Eye

Abstract: Purpose: To report the safety and efficacy of intravitreal bevacizumab (IVB) in a case of cystoid macular edema (CME) in a silicone oil-filled eye.Methods: A man, aged 51 years, reported with poor visual improvement in the right eye (RE) after pars plana vitrectomy with oil injection performed 2 months back for a pseudophakic, macula-off rhegmatogenous retinal detachment. His best-corrected visual acuity in the RE was counting fingers 2 m. Fundus examination of the RE showed a silicone oil-filled eye with atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A case report by Lambat et al 26 described intravitreal bevacizumab to treat CME under SO, resulting in significant improvement of VA and complete resolution of CME within a week of the injection. Another case report by An and Kim 27 described the use of intravitreal dexamethasone implants, which were not effective before SOR but improved VA and CFT after SOR.…”
Section: Discussionmentioning
confidence: 99%
“…A case report by Lambat et al 26 described intravitreal bevacizumab to treat CME under SO, resulting in significant improvement of VA and complete resolution of CME within a week of the injection. Another case report by An and Kim 27 described the use of intravitreal dexamethasone implants, which were not effective before SOR but improved VA and CFT after SOR.…”
Section: Discussionmentioning
confidence: 99%
“…Lambat et al reported a case of cystoid macular edema resolved and visual acuity improved in a silicone oil-lled eye treated with an intravitreal injection of bevacizumab [14]. However, there is only one case.…”
Section: Discussionmentioning
confidence: 99%